When Teleology Fails: Aristotle on Bile as a Useless Residue in Parts of Animals. - Ezrohi, Dmitry (Scripta Classica Israelica, 2023)
Aristotle provides no clear justification for his unique position on the status of bile (χολή). He argues against established tradition and his usual teleological framework that this substance has no function but is a useless residue of the liver. Moreover, the basis for Aristotle's critique of two competing views about bile, that of Plato's Timaeus and the followers of Anaxagoras, has not been fully elucidated. In this paper, I argue that Aristotle's arguments against his predecessors and his non-teleological account of bile are firmly based on anatomical data, specifically from non-human animals. I show that the structure of the exposition of anatomical details and the role comparative anatomy plays in his argument reveal Aristotle's concerns both with the content of his predecessors' physiological explanations and also with their anthropocentric and noncomparative methodology.